2011
DOI: 10.1271/bbb.100722
|View full text |Cite
|
Sign up to set email alerts
|

Potential ofD-erythro-C14-Sphingosine as an Adjuvant for a Fungal Pesticide ofNomuraea rileyi

Abstract: D-erythro-C(14)-Sphingosin (C(14)-Sph) was isolated as the germination accelerating factor in Nomuraea rileyi in our previous study. This activity was expected to support fungal infection by reduction of the infection time between conidial adhesion and invasion into the insect. In this study, we estimated the effect of C(14)-Sph with regard to the infection time. Conidia activated by C(14)-Sph shortened the time to about half, indicating the potential of C(14)-Sph as an adjuvant for fungal pesticide of N. rile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A total of 12.4 mg of a substance (GAF) was isolated in the active fraction. 7) This isolated GAF was subjected to structural analyses. 10) It was found that GAF had the erythro (rel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 12.4 mg of a substance (GAF) was isolated in the active fraction. 7) This isolated GAF was subjected to structural analyses. 10) It was found that GAF had the erythro (rel.…”
Section: Resultsmentioning
confidence: 99%
“…7) This leads to the hypothesis that an inactive precursor was present that produced active degradation products by the methanolysis digestion. The results of the present study reveal that GAF was probably C 14 -Sph.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations